Epistemic Modality in Georgian - Sharashenidze, Nino (Verbum, 2015)
The epistemic modality consists of epistemic possibility and necessity. Particle “Unda” (must) is the main formative of the epistemic necessity. Originating from a notional verb, it still retains its verbal functions. In the conjugation of an object, “Unda” is the III person form. It means “wish”, “want”. However, in modern Georgian, it is a multifunctional particle, with the epistemic necessity being one of the meanings thereof. “Unda” is associated with a verb in the subjunctive mood and expresses the speaker’s opinion, evaluation and attitude to the reality, the speaker’s assumption, conviction or the lack thereof. The said modality expresses intellectual perception of the speaker. Sentence1.“ის ახლა სახლში უნდა იყოს” [is axla saxlshi unda ix’os] – He must be at home now. “Unda” (must) expresses the speaker’s certainty ensuing from the analytical assessment of reality. The sentence implies his belief that someone must be at home since it is the most logical possibility based on the fact that lights are on. 2. “მას კარგად უნდა გაეკეთებინა ეს საქმე” [mas k’argad unda gaek’etebina es sakme] – He must have done a good job of it. Here “Unda” implies that as far as I know him, his capabilities and sense of responsibility, I believe that he must have got on with the job well enough. So, the epistemic necessity is expressed by “Unda” modal particle and a verb in the subjunctive mood and implies a logical necessity based on the speaker’s belief. In the determination of the epistemic modality, not only the analysis of the modal particle and a verb matters but the definition of the semantic groups of the verbs involved in the pattern. The paper will contain the functional and semantic analysis of the patterns expressing the aepistemic necessity.